Tanggung Jawab Negara Terhadap Pelanggaran Kemanusiaan Suku Aborigin Sebagai Indigenous People - Dahalia Fatima Toekan; Johanis Steny Franco Peilouw; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Aboriginal people are indigenous and constitute a minority population in Australia and are known as Indigenous Peoples.When the white people arrived in Australia, they took over the land rights of the aboriginals.Purposes of the Research: To find out how international law in providing protection for aboriginal tribes who are indigenous people and knowing and understanding the form of the Australian state's responsibility for humanitarian violations for aboriginal tribes as indigenous people. Methods of the Research: This research isnormative juridical law research, with primary and secondary legal materials as legal sources. Furthermore, it was analyzed qualitatively.Results of the Research: The results of this study indicate thatprotection for aboriginal tribes as Indigenous Peoples is regulated in the International Labor Organization (ILO) Convention No. 169 of 1989, the United Nations Declaration of Rights on the Indigenous Peoples (UNDRIP) Convention in 1984 and the Indigenous Peoples Rights Act (IPRA) Convention in 1997.As a form of responsibility, Australia has signed various international treaties and conventions on human rights and as a form of state responsibility for violations of humanity of aboriginal tribes as aIndigenous Peoplesby formingThe Council for Aboriginal Reconciliationin 1992 and then apologized nationwide in February 2008